Using a Group Exercise to Teach About the Hidden Curriculum - Kathleen Crapanzano; Ann Schwartz; Jacob Sperber; Susan Stagno; Lannis Tynes (Association of American Medical Colleges, 2015)
Abstract Introduction Whether positive or negative, the hidden curriculum is a powerful force in residents' professional formation and one place where professionalism is learned. As opposed to the explicit didactic curriculum or the implicit bedside teaching that goes on during rounds, the hidden curriculum reflects the culture of the environment in which a resident works. This exercise familiarizes participants with a scenario demonstrating a negative hidden curriculum and allows them to develop a deeper understanding of the impact of the hidden curriculum on learners as well as patients. Methods This role-play is a 20-minute small-group activity designed to teach the meaning of the hidden curriculum in medical education. Volunteers from the learner group choose a part in the role-play and read from the script. While they stand under their character names in front of projected PowerPoint slides, thought bubbles appear over their heads, demonstrating what the characters are thinking. After the role-play, the group discusses the role-play scenario, its relevance, and its implications. At the completion of the exercise, learners are asked to complete a commitment-to-change card, putting in writing any change in behavior that they anticipate as a result of the experience. Results We used this play exercise in a national workshop as an icebreaker. It was well received and instantly allowed participants to understand what is meant by the hidden curriculum and why it can affect our learners. Three months later, we followed up with the workshop participants. Of those who responded to our query (about 30% of attendees), virtually all had reflected on the lessons of the workshop and made some level of change to their thinking and behavior. Discussion This exercise mimics clinical scenarios that learners can relate to. It also allows the instructor to teach about the hidden curriculum without preaching. The script provided is a psychiatric one but could be adjusted to accommodate other specialties as well.